Magnetic Reconnection: An Alternative Explanation of Radio Emission in Galaxy Clusters - Subham Ghosh; Pallavi Bhat (The Astrophysical Journal Letters)
Observations of galaxy clusters show radio emission extended over almost the system scale, necessitating mechanisms for particle acceleration. Previous models for acceleration, such as diffusive shock acceleration and that due to turbulence, can fall short in terms of efficiency. In this Letter, we propose the possibility of acceleration via magnetic reconnection. In particular, we invoke the plasmoid instability, which has been previously applied to understand particle energization in high-energy systems. Turbulence in galaxy clusters leads to fluctuation dynamos that are known to generate magnetic field structures consisting of sharp reversals. These form natural sites of reconnection. We perform particle-in-cell simulations of the plasmoid instability in collisionless and nonrelativistic plasmas. We show that the resulting electron energy spectra have power-law indices that are consistent with those inferred from observations. Our estimates show that the acceleration timescales are much smaller than the lifetime of the reconnecting magnetic structures indicating the feasibility of our model. The synchrotron radio luminosity estimate is about 10 ^41 erg s ^−1 , agreeing with observations. Finally, we find that the maximum achievable Lorentz factor can go up to 10 ^5 indicating that acceleration due to magnetic reconnection is a promising avenue for understanding the origin of nonthermal emission in galaxy clusters.